QUALITY METRIC DESIGN USING INTERNAL CONTROL METHOD TO CONTROL THE QUALITY OF FIBER OPTIC INSTALLATION PROJECT - Abdurrahman, Ahmad Fauzan; Delvika, Rizka Hasna; Haryono, Imam; Pratami, Devi; Bermano, Ageak Raporte (International Journal of Innovation in Enterprise System, 2019)
To provide internet network, one of public Telecommunication provider in Indonesia conduct several project related to fiber optic cable installation such as the STO Modernization Feeder project. In every project implementation, the company is concerned with quality in order to remain competitive with competitors. Deliverable which meets the project quality will produce the product in accordance with the requirements. STO Garut Feeder Modernization Project was experiencing delays which is caused by the non-conformity project deliverable to project specification during monitoring & controlling phase. At project planning, the quality metric was not designed, which can be used as a guideline for vendor in carrying out the project task and to assist the process of quality control. Quality metric design is carried out using internal control methods that can identify possible errors in each project activity and critical success criteria that define a successful activity that will be performed. Result shows that only 67.1% statement (critical success criteria) form critical activity is implemented. This result can answer why the project delay because the activity on critical path is mostly re-worked due to non-conformity issues. Keywords—Quality, quality metric, internal control, control quality, telecommunication project